Effects of artificial light at night and drought on the photosynthesis and physiological traits of two urban plants - Wei, Yaxi; Li, Zhen; Zhang, Jiaolong; Hu, Dan (Frontiers in Plant Science, 2023)
Urban plants are currently confronted with the stresses posed by artificial light at night (ALAN) and drought. A field block experiment was designed to explore the potential effects of ALAN and drought on the photosynthesis and physiological characters of two common urban plants, Euonymus japonicus (E. japonicus) and Rosa hybrida (R. hybrida). Each plant species was subjected to four distinct treatments: neither ALAN nor drought, ALAN, drought and both ALAN and drought. The result showed that (1) ALAN significantly reduced the effective quantum yield (ΦPSⅡ), apparent electron transfer rate (ETR), photochemical quenching parameter (qp), net photosynthetic (Pn), stomatal conductance (Gs), stomatal limit value (Ls) and the pigment concentrations and remarkably increased the content of malondialdehyde (MDA), total antioxidant capacity (TAC), and starch in both E. japonicus and R. hybrida. Furthermore, ALAN increased the soluble saccharides of E. japonicus and this effect of ALAN also occurred on R. hybrida under drought; (2) Drought significantly decreased the ΦPSⅡ, ETR, qp, Pn, Gs, Ls and the pigment concentrations and remarkably increased the content of MDA, TAC for both E. japonicus and R. hybrida. Besides, drought did not significantly change the starch content of both the species, and it significantly increased the content of soluble saccharides for E. japonicus; (3) The interaction between ALAN and drought occurred on the ΦPSⅡ, ETR, Pn, MDA and TAC of E. japonicus, but had no effect on R. hybrida. For urban areas affected by ALAN and drought, it is advisable to select plant species with strong stress resistance for gardening purposes, and plants directly exposed to ALAN should receive sufficient watering during hot and dry weather conditions to maintain their normal growth.